2006
DOI: 10.1029/2006rs003472
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Joule heating by lightning continuing current inferred from radio remote sensing

Abstract: [1] The mean lightning current waveform of particularly intense lightning discharges is inferred from 52,510 radio wave recordings in the frequency range 1-200 Hz. The current waveform decays initially with a time constant of $2 ms, and the current lowers $60 C from cloud to ground within the first $10 ms of the discharge. The subsequent continuing current exhibits a decay time constant of $40 ms and lowers $170 C from cloud to ground within the next $100 ms of the discharge. The total charge transfer $230 C f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The importance of a strong lightning continuing current in the production of TLEs has also been noted by Fu¨llekrug et al (2006a).…”
Section: Article In Pressmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance of a strong lightning continuing current in the production of TLEs has also been noted by Fu¨llekrug et al (2006a).…”
Section: Article In Pressmentioning
confidence: 95%
“…6(a). The total charge transferred to ground by this þCG discharge is $67 C. (Price et al, 1997 took a value of 43 C.) Fu¨llekrug et al (2006a), investigating particularly intense lightning discharges, showed that the total charge transferred from cloud to ground by one þCG discharge was $230 C. The change in the ionospheric potential caused by the þCG is shown in Fig. 6(b): the potential decreases by 41 V from 300 kV in $20 s, and recovers in $250 s. The magnitude of the fairweather electric field decreases by 16 mV/m and recovers to the initial value in the same time.…”
Section: A Positive Cloud-to-ground Dischargementioning
confidence: 99%
“…A mean lightning current waveform was inferred from the recordings of 52,510 intense lightning discharges (Füllekrug et al 2006b) made with a global network of ELF magnetometers (Füllekrug and Constable 2000). It was found that the lightning current initially decays with a time constant of *2 ms and that it lowers *60 C from cloud to ground within the first *10 ms of the discharge.…”
Section: Radiation At Elfmentioning
confidence: 99%
“…Only very few −CG‐triggered sprites have been reported [ Barrington‐Leigh et al , 1999; Williams et al , 2007]. +CG flashes support continuing currents up to a few kiloamperes (kA) which can last a few hundred milliseconds [e.g., Rust et al , 1985; Bell et al , 1998; Cummer and Füllekrug , 2001; Füllekrug et al , 2006; Campos et al , 2009], so that large amounts of charge can be drained from the cloud. In response to the charge removal, a transient electric field develops between the cloud and the ionosphere.…”
Section: Introductionmentioning
confidence: 99%